Gambaran Perkembangan Anak Stunting Usia 24-36 Bulan di Wilayah Kerja Puskesmas Oemasi Kecamatan Nekamese - Pratama, Siti Ratna Putri (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2024)
Backround Stunting is an increasingly common problem, there are 195 million children living in poor and developing countries experiencing stunting. The incidence of stunting in Indonesia in children under five is 30.8% with very short criteria 11.5% and short 19.3%. The high rate of stunting in East Nusa Tenggara causes chronic malnutrition to occur in children. The risk of malnutrition that can occur is developmental disorders in children. Objective To get an overview of the development of stunting children aged 24-36 months in the work area of the Oemasi Health Center, Nekamese District. Methods The research used was descriptive analysis with a sample of 51 stunting children. Sampling was done by total sampling technique. The data collection instrument used a Developmental Pre-Screening Questionnaire. Results The study showed that most of the respondents had doubtful fine motor development (51.0%), doubtful gross motor skills (51.0%), poor language speech (51.0%) and doubtful self-reliance socialization (47.1%). Conclusion From the results of the study, it can be concluded that stunting children aged 24-36 months in the work area of the Oemasi Health Center, Nekamese District experienced more dubious developments. Keywords: Development, Stunting